Evaluating the repetitive mucus extraction effects on mucus biomarkers, mucous cells, and the skin-barrier status in a marine fish model - Sanahuja, Ignasi; Guerreiro, Pedro M.; Girons, Albert; Fernandez-Alacid, Laura; Ibarz, Antoni (Frontiers in Marine Science, 2023)
Among all the mucosal barriers, the skin and its surrounding mucus are possibly the main defensive tool against the environment in fish. Due to the extraction of this mucus being less invasive, the study of its production and functions has attracted great interest in recent years. However, there are still many gaps concerning the sampling process as well as the possible alterations in skin integrity and mucus composition. In the current study, the effects of skin mucus extraction were determined by comparing the effects of a single extraction (single extraction group, SEG) with those of three successive extractions separated by 3 days (repetitive extractions group, REG). Intact skin histology without mucus extraction (ØEG) and both plasma and skin mucus biomarkers and antibacterial capacities were also assessed. Regarding the skin histology and skin barrier properties, both the SEG and REG did not show differences in the intact skin. Interestingly, repetitive mucus extractions seemed to activate skin mucus turnover, significantly increasing the number of small-sized mucous cells (cell area < 100 µm2) and reducing the number of large-sized mucous cells (cell area > 150 µm2). Repetitive extractions significantly decreased the amounts of soluble protein and increased cortisol secretion. These metabolites remained unaltered in the plasma, indicating different responses in the plasma and mucus. Despite changes in the mucus biomarkers, antibacterial capacity against pathogenic bacteria (Pseudomonas anguilliseptica and Vibrio anguillarum) was maintained in both the plasma and mucus irrespective of the number of mucus extractions. Overall, the mucus sampling protocol had little effect on skin integrity and mucus antibacterial properties, only modifying the amounts of soluble protein exuded and stimulating mucous cell replacement. This protocol is a feasible and minimally invasive way of studying and monitoring fish health and welfare and can be used as an alternative or a complement to plasma analysis. This methodology can be transferred to farm culture conditions and be very useful for studying threatened species in order to preserve fish welfare.